Conceptualizing Suicidal Ideation Among Firefighters Through the Lens of an Integrated Theoretical Model. (July 2021) - Henderson, Elizabeth; Guthrie, Barbara J.
Suicide is the 10th leading cause of death in the United States and is a major concern among professional American firefighters, with rates for suicidal ideation in firefighters two times higher than rates in the general population. The Neuman systems model integrated with the interpersonal-psychological theory of suicide provides a better understanding of the specific occupational and cultural aspects of firefighting that lead to a greater risk for suicidal ideation. This model provides an innovative lens that can inform the development and the implementation of interventions aimed at preventing suicidal ideation among firefighters.